Pemeriksaan Asam Urat, Gula Darah dan Tekanan Darah sebagai Deteksi Dini Penyakit Tidak Menular pada Masyarakat Baduy Lebak - Banten - Erma Noor Wahyuningsih; Heny Sasmita; Ucu Wandi Somantri; Mega Nurlela; Ahmad Ruyani; Tri Widya Utami; Intan Permata Sari (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Non-communicable diseases (NCDs) are major public health problems that develop slowly and are often asymptomatic in the early stages. The Baduy community has limited access to modern health services, resulting in a lack of routine health screening. This community service activity aimed to conduct health screening through uric acid, blood sugar, and blood pressure examinations as an effort for early detection of NCDs in the Baduy community of Kanekes Village, Lebak Regency, Banten. The activity methods included preparation, health examinations, health education, and evaluation. A total of 17 community members participated in the activity. The results showed that 41.2% of participants had elevated uric acid levels, 11.8% had high blood sugar levels, and 47.1% had high blood pressure. This activity increased community awareness of the importance of routine health checks and provided an initial overview of NCD risk factors. Health screening combined with education is expected to contribute to the prevention of NCDs and improvement of community quality of life.